Nitrous oxide emissions in corn (Zea mays L) as affected by timing, method of application and source of dairy manure. - Cambareri, Gustavo Sebastián (2018)
Thesis Doctor of Philosophy in Environmental Sciences in University of Guelph, Ontario, Canada. 2016